Investigating Themes That Are Embedded in Dagaaba Proverbs - Kogri, Eugene Naah; Aduko, Patrick Atanga (Advances in Social Sciences Research Journal, 2023)
A plethora of literature exist about proverbs in general and Dagaaba proverbs in particular but, little is said about the themes that are embedded in them with particular reference to the central dialect of Dagaare. It is very important to note that, the central dialect or otherwise the standard dialect of Dagaare is used for academic and examination purposes. This paper therefore seeks to investigate the concept and functions of proverbs and critically examine the themes that are embedded in Dagaaba proverbs. The functions of proverbs are put into two; didactic and aesthetic. The themes have been clearly explained in the work. A purposive sampling technique was implemented and the design of the research was qualitative. The research framework was content analysis since the data analysis was mainly descriptive. The sample population for the study was focused on three (3) language communities in Ulkpong Traditional area of the Upper West Region of Ghana. The instruments used for data collection were unstructured interview and participatory observation. Eight themes were identified in the proverbs. The theme of patience and perseverance, appreciation, unity, laziness, indiscipline, ignorance, hard work and greed were chosen because of their importance to human and national development. Proverbs are general seen as a cultural heritage, which is held in high regard since it is generally believed that the philosophy, value system, wisdom and knowledge of the society are embedded in them. The findings confirmed that Dagaaba proverbs have various themes as far as their contextual usage is concerned.